2021
DOI: 10.1186/s12870-021-03159-3
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress introduces growth, physiological traits and ecological stoichiometry changes in two contrasting Cunninghamia lanceolata cultivars planted in continuous-plantation soils

Abstract: Background The decrease in Cunninghamia lanceolata (Lamb.) production on continuously planted soil is an essential problem. In this study, two-year-old seedlings of two cultivars (a normal cultivar, NC, and a super cultivar, SC) were grown in two types of soil (not planted (NP) soil; continuously planted (CP) soil) with three watering regimes, and the interactive effects on plant growth and physiological traits were investigated in a greenhouse experiment. The water contents of the soil in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, decreasing growth rate of two types of oak tree seedlings (Quercus cerris and Quercus robur) under drought stress was observed in a study by Deligoz and Bayar (2018). Bian et al (2021) showed that stem height and stem diameter of Cunninghamia lanceolata significantly reduced when the seedlings grown under low water content condition compared with well-watered condition. Nonsignificant effects with applying mulching treatments (P > 0.05) was observed on the survival percentage, increments of stem height, stem diameter and leaf number (Table 2).…”
Section: Resultsmentioning
confidence: 91%
“…In addition, decreasing growth rate of two types of oak tree seedlings (Quercus cerris and Quercus robur) under drought stress was observed in a study by Deligoz and Bayar (2018). Bian et al (2021) showed that stem height and stem diameter of Cunninghamia lanceolata significantly reduced when the seedlings grown under low water content condition compared with well-watered condition. Nonsignificant effects with applying mulching treatments (P > 0.05) was observed on the survival percentage, increments of stem height, stem diameter and leaf number (Table 2).…”
Section: Resultsmentioning
confidence: 91%
“…Cunninghamia lanceolata (Chinese fir), an evergreen coniferous tree mainly distributed in southern China [ 5 ], is one of the most important timber trees with great commercial value due to its fast growth rate, high yield, high quality and pest resistance [ 6 , 7 ]. However, frequent occurrences of extreme drought and high temperature events are becoming great risks for growth and biomass production of Chinese fir [ 8 10 ]. Therefore, it is an important subject to select or breed drought and high temperature resistant varieties for breeders of Chinese fir.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is an important subject to select or breed drought and high temperature resistant varieties for breeders of Chinese fir. Although there was a long breeding history, artificial selection on stress-resistant varieties of Chinese fir still relies on expert visual observation and physiological measurements [ 8 , 11 ], which are time-consuming, labor-intensive, costly and prone to human error. To develop an efficient, automated and accurate method for evaluation and classification on growth status is of great significance to stress-resistant varieties selection and breeding in Chinese fir.…”
Section: Introductionmentioning
confidence: 99%
“…Hook (C. lanceolata) [43]. C. lanceolata, as endemic and evergreen coniferous species, is one of the most important artificial timber forest species in southern China because of its high timber quality and fast growth [43,44]. C. lanceolata is gradually suffering from increased stress, including temperature [45], drought stress [46], and autotoxicity caused by allelopathic toxins such as phenolic acids [47].…”
Section: Introductionmentioning
confidence: 99%